Tumour related epilepsy: an integrated management approach. (31st January 2018) - Mullens, Laura; Cikurel, Katia; Maccoll, Jillian; Hurwitz, Victoria; Ford, Liz; La, Jess; Ashkan, Keyoumars
Abstract: INTRODUCTION: In patients with brain tumours, seizures are common. 90% of patients with gangliogliomas and DNET tumours and 80% of patients with diffused low-grade gliomas could experience seizures at some point during their disease. Whereas, 50% of patients with high-grade glioma could develop seizures. This leads to a large neurology workload which is managed at Kings College Hospital (KCH) by an integrated service of a Neurologist and Clinical Nurse Specialists. OBJECTIVE: To examine the practice provided to patients with tumour related epilepsy by the integrated service at KCH and assess how our service benefits patients, avoids GP/A&E visits and reduces hospital admissions. METHOD: Four-month data collection grouped and presented into categories. RESULTS: 86 patients had contact with the integrated neuro-oncology team regarding neurology needs from 1 November 2016 to 28 February 2017: 51% required review in clinic only15% required a clinic review with email/telephone input34% were supported via email/telephone input alone21% required more than one visit31% had a diagnosis of a low-grade glioma, 22% of a high-grade glioma, 22% of a meningioma 14% attended A&E/admitted to hospital despite our advice Of those patients supported by email/telephone alone: 78% were contacted by telephone, 22% via email63% reported seizure activity, 37% had medication queries 29% attended A&E/admitted to hospital despite our advice71% avoided hospital/GP appointments and/or attending A&E CONCLUSION: Tumour related epilepsy data provided from a large neuro-oncology service at KCH is worthy of being shared. It can highlight the importance of an integrated neuro-oncology service which is accessible to patients through various means: email, telephone, clinics. A personalized service adjusted to the needs of patients. Moreover by utilising the expertise of the Neurologist we have shown that an integrated service may reduce the use of hard-pressed NHS resources in primary care settings and within hospitals.